INFLUENCE OF PHYSIQUE ON THE PHYSICAL FITNESS OF PEDAGOGICAL UNIVERSITY STUDENTS - Bogdanov, O.A.; Komissarova, E.N.; Tsipin, L.L.; Samsonova, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the dependence of the level of physical fitness of male students of a pedagogical university on the indicators of physique. Methods and structure of the study. The experiment involved 43 first-year students of The Herzen State Pedagogical University of Russia at the age of 18-20 years, classified for health reasons to the main and preparatory medical groups. Body length and weight, body mass index, and percentage of body fat were measured as indicators of physique, which was calculated according to a standard method based on the thickness of skin-fat folds. The following tests were used to assess physical fitness: running 60 and 3000 m, pulling up on a high crossbar, lifting legs to the crossbar from a hanging position, long jump from a place, bending forward while standing on a gymnastic bench. Testing and measurement of physique indicators were carried out at the end of the second semester. Results and conclusions. It was found that the body mass index of students is normal, and the percentage of fat in the body is above the norm (22.9±1.1%). It follows from this that when determining the compliance of body weight with the norm, the calculation of only the body mass index is insufficient - it is also necessary to take into account body composition. The test results showed the average level of students' physical fitness. Physique indicators significantly affect the results of tests that evaluate the speed and strength abilities of students. In this case, the correlation coefficient ranges from -0.61 to 0.52, with body fat having the greatest effect. However, the correlation of physique indicators with the results of tests for endurance, speed-strength abilities and flexibility turned out to be unreliable (p>0.05). The regularities obtained can serve as a basis for the development of physical culture programs for students, taking into account the need to correct the body composition of those involved.